Stimulated whole-blood cytokine/chemokine responses are associated with interstitial cystitis/bladder pain syndrome phenotypes and features of nociplastic pain: a multidisciplinary approach to the study of chronic pelvic pain research network study. Issue 5 (19th May 2023) - Schrepf, Andrew; Kaplan, Chelsea; Harris, Richard E.; Williams, David A.; Clauw, Daniel J.; As-Sanie, Sawsan; Till, Sara; Clemens, J. Quentin; Rodriguez, Larissa V.; Van Bokhoven, Adrie; Landis, Richard; Gallop, Robert; et al.
Abstract : Supplemental Digital Content is Available in the Text. Inflammatory responses to toll-like receptor stimulation of whole blood are associated with nociplastic pain features in women with interstitial cystitis/bladder pain syndrome. Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a common and debilitating disease with poor treatment outcomes. Studies from the multidisciplinary approach to the study of chronic pelvic pain research network established that IC/BPS patients with chronic overlapping pain conditions (COPCs) experience poorer quality of life and more severe symptoms, yet the neurobiological correlates of this subtype are largely unknown. We previously showed that ex vivo toll-like receptor 4 (TLR4) cytokine/chemokine release is associated with the presence of COPCs, as well as widespread pain and experimental pain sensitivity women with IC/BPS. Here, we attempt to confirm these findings in the multisite multidisciplinary approach to the study of chronic pelvic pain Symptom Patterns Study using TLR4-stimulated whole blood (female IC/BPS patients with COPC n = 99; without n = 36). Samples were collected in tubes preloaded with TLR4 agonist, incubated for 24 hours, and resulting supernatant assayed for 7 cytokines/chemokines. These were subject to a principal components analysis and the resulting components used as dependent variables in general linear models. Controlling for patient age, body mass index, and site of collection, we found that greater ex vivo TLR4-stimulated cytokine/chemokine release was associated with the presence of COPCs ( P < 0.01), extent of widespread pain ( P < 0.05), but not experimental pain sensitivity ( P > 0.05). However, a second component of anti-inflammatory, regulatory, and chemotactic activity was associated with reduced pain sensitivity ( P < 0.01). These results confirm that the IC/BPS + COPCs subtype show higher levels of ex vivo TLR4 cytokine/chemokine release and support a link between immune priming and nociplastic pain in IC/BPS.